Evaluasi Kesuksesan Penerapan Sistem Informasi di LPPM STMIK STIKOM Indonesia - Sandika, I Kadek Budi; Hamid, Hamid (P3M Politeknik Negeri Banjarmasin, 2021)
Information systems that have been developed and used need to be evaluated. Measuring the success of the application of an information system must take into account at least four parameters, namely the individual who uses it, the organization where individuals interact, the information the system presents, and the information technology itself. This study also examined whether there is a direct correlation between user experience and organizational support for net benefits. This research was carried out in three stages, from the preparation, data collection, to data analysis and reporting. Based on the results of testing the research hypothesis, only one hypothesis was accepted (significant), namely the relationship between the quality of information systems, the use of information systems, user satisfaction and net profits. Based on the results of testing and discussion, the application (sitasi) is still not fully successful. There are several obstacles found in its operations, both in terms of system quality, information quality, and the quality of citation services